The Essence of Person-Based Learning in Continuous Professional Development of the Teacher - Sharipboevna, Fayzullaeva Gulchekhra (Researchparks Publishing, 2023)
The article describes views and theories of person – oriented education and person – based learning, as well as their role in continuous professional development of the teacher and finding solutions to problems in his work. Also, a comparative table was formed based on the summarization and analysis of research on these two concepts.